Impact of workplace environment on health of leather factory workers - Yogaraj G., Arunkumar; Ravi, Rama (International Journal Of Community Medicine And Public Health, 2017)
Background: The working environment and basic facilities available in the workplace have impact on physical and psychological health of leather workers. The objective was to study the effect of workplace environment on health of leather workers. Methods: A cross section study was carried out in eight permitted leather factories at rural area in Sripuram near Chromepet, Chennai. Using a pretested scheduled questionnaire, 230 workers were interviewed, their corresponding socio-demographic profile was collected and various health scores were recorded based on the general and physical examination. Scoring technique and student ‘t’ test was used to identify the correlation and degree of association between workplace environmental factors and health status of workers. Results: The scoring technique and correlation coefficient revealed an association between workplace health status and clinical symptoms (p<0.001), duration of work and clinical symptom scores (p=0.001), duration of work and workplace health (p<0.001), Workplace health status and occupation (t-test value 5.562, p<0.001), and facilities available and occupation (t value 3.758, p<0.001). Conclusions: The above results show the impact of workplace environment on the health status of workers and require adequate measure to improve the facilities and thereby the health status of workers.